Georesistivity assessment of lithological and hydrodynamic factors in groundwater sanitation of Akwa Ibom river channel aquifer system - Kufre Richard Ekanem; Nyakno Jimmy George; Aniekan Martin Ekanem; Ndifreke Inyang Udosen; Jewel Emem Thomas (Geosystems and Geoenvironment, 2025)
This study deploys methods of vertical electrical sounding (VES), electrical resistivity tomography (ERT), and georesistivity-hydrodynamic correlation to evaluate groundwater quality and lithological changes in the river channel aquifer system of Akwa Ibom State, Southern Nigeria. In addition to revealing groundwater recharge and discharge zones, resistivity anomalies combined with borehole lithology also highlight the potential for contamination from rivers, landfills, and agricultural runoff. According to georesistivity studies, there are four different subsurface layers. The topmost layer shows resistivity fluctuations between 14.1 and 2345.4 Ωm (mean: 501.1 Ωm, CV: 105%), which are caused by human activity and surface erosion. High thickness variations (1.8–102.8 m) and resistivity values (8.1–1847.1 Ωm) are observed in the second layer, a fine sand aquifer. Medium to coarse sands make up the third layer, which exhibits resistivity values ranging from 1.1 to 2408.9 Ωm (CV: 124%). Although the thickness of the fourth layer is unknown, its resistivity values range from 12.3 to 2128.2 Ωm. 40.7% of the region is made up of high-energy aquifers (HK: ρ1 > ρ2 < ρ3 > ρ4), 14.8% are Q-type (ρ1 > ρ2 > ρ3), and 14.8% are H-type (ρ1 < ρ2 > ρ3), according to VES curve classifications. These conditions imply high permeability, transmissivity, and groundwater flow, all of which jeopardize groundwater sanitation. The percentage of sampling sites with low-energy aquifers with limited storage capacity is just 3.7%. High-resistivity zones correlate to compacted formations, whereas low-resistivity zones near river channels are identified as active recharging locations using resistivity mapping. It is confirmed by borehole lithology that fine, gravelly sands predominate in groundwater-bearing units. Hydraulic conductivity, permeability, and transmissivity range from 0.52 to 31.45 m/day, 788.39 to 51,681.97 mD, and 18.72 to 1988.27 m²/day, respectively, according to hydrodynamic study. The Dar Zarouk characteristics, which range from 0.015 to 7.194 Ω⁻¹ for longitudinal conductance, categorize protective capacities as dominantly weak (63%), moderate (15%), good (11%), or very good (11%). Overall, this study demonstrates how intricately groundwater quality, hydrodynamics, and lithology interact within the river channel aquifer system. As inferred from the results, significant binary correlations exist between depth and aquifer thickness, water resistivity and bulk resistivity, transverse resistance and bulk resistivity, longitudinal conductance and bulk resistivity, as well as water resistivity and transverse resistance. Moreover, hydraulic conductivity exhibits a strong correlation with both permeability and transmissibility. In Nigeria's coastal aquifers, the results shed light on pollution hazards, groundwater recharge efficiency, and methods for managing water resources sustainably.